(untitled) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2017)
The Authors analyze the infectious bovine rhinotracheitis (IBR), in order to clinically classify the disease, and examine the animal health legislation of Italy and Veneto in relation to the cost-benefit costs of the control programmes. IBR is a not notifiable disease neither in Italy nor in EU, according with Regulation n. 429/2016.